Andragogical foundations of postgraduate education institutions students’ independent work - PosokhovaI, S. (Problems of Engineer-Pedagogical Education, 2018)
Basing on fundamental andragogical conceptions (priority of students’ independent educational and cognitive activity; individualization of studying; elective approach, attitude to studying with choice; development of students’ educational needs; student’s organization his or her actions devoted to educational process’organization) in the article the basis of organization adults’ independent work which is conducted step-by-step was singled out. The content and results of such stages of independent work organization as student’s readiness for its completion diagnostics, planning, creation conditions for process’ realization, independent completion of work by a student, evaluation and correction of educational achievements were determined. Some questionnaires for students’ self-evaluation of knowledge about how to complete the work on reproductive, cognitive-search and creative levels of cognitive activeness and independence and forming the skills of its completion (to formulate the aim, to manage independently, to control, to correct its completion, to evaluate the results) were worked out. The questionnaires can be used at all stages of independent work.